Tending the Gardens of Citizenship: Child Saving in Toronto, 1880s-1920s - Finkel, Alvin (Labour / Le Travail, 2006)
The article reviews the book, "Tending the Gardens of Citizenship: Child Saving in Toronto, 1880s-1920s," by Xiaobei Chen.
Keywords: BOOKS -- Reviews; CHEN, Xiaobei; Nonfiction; Sociology; TENDING the Gardens of Citizenship: Child Saving in Toronto 1880s-1920s (Book)